Daisy: A high-yielding and early maturing mandarin for Thar desert - Gora, Jagan Singh; Kumar, Ramesh (Indian Horticulture, 2024)
Daisy is an interspecific hybrid cultivar of mandarin and is known for its high yield, attractive dark orange fruit peel colour, and tasty juice. Its plant growth is medium in size with a drooping canopy and leaves (thick, larger, and slightly folding nature). These distinctive morphological characteristics make it well suited for high-density planting and water-deficit conditions. It produces medium-largesized, juicy, sweet, less-seeded fruits exhibiting dark orange, thin and glossy peel along with unique flavour. The better yield, attractive, sweet and juicy fruits mature in lean period (a gap between sweet orange and kinnow mandarin supply in market). It gives early quality marketable harvest in November month in the arid region may increase farm income, and farmers can adapt an alternative source in place of Kinnow mandarin, which is suffering from a market glut with a lower fruit price in current scenario.